Finansial and Performa Analysis Institute Support Development of Subsistem Downstream Agribisnis in Metro - Sri Indaryati; Dayang Berliana (Politeknik Negeri Lampung., 2021)
Agriculture policy in downstream sector area mechanize of agriculture is adequate not yet. Institute service restructuring and enableness of farmer through enableness of local institute and also farmer organization represent effort overcome dificulty of institute gapoktan. Method of the research with sampling random startified and descriptive qualitative with case study desain, compose primary data and sekunder data. Elegibility effort of agribisnis downstream service activities management of competent Rice miling Unit category there are group melati 2 NPV=5,31, Net B /C=3,67, Gross of B/C=6,33, IRR=15%, Pp=1,96 and of ROI 8,53 Year.